2017
DOI: 10.3390/toxins9080247
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Entry of Clostridium perfringens Iota-Toxin and Clostridium botulinum C2 Toxin

Abstract: Clostridium perfringens iota-toxin and Clostridium botulinum C2 toxin are composed of two non-linked proteins, one being the enzymatic component and the other being the binding/translocation component. These latter components recognize specific receptors and oligomerize in plasma membrane lipid-rafts, mediating the uptake of the enzymatic component into the cytosol. Enzymatic components induce actin cytoskeleton disorganization through the ADP-ribosylation of actin and are responsible for cell rounding and dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(77 citation statements)
references
References 51 publications
(129 reference statements)
0
76
0
1
Order By: Relevance
“…Clostridium perfringens iota toxin consists of two distinct protein components, one being the cell-binding protein (Ib) and other the enzymatic protein (Ia) [ 1 , 2 , 3 , 4 , 5 , 6 ]. Ia possesses actin-ADP-ribosyltransferase activity, blocking the formation of F-actin in the cytosol and then disrupting the actin cytoskeleton [ 2 , 6 , 7 , 8 ]. It has been reported that lipolysis-stimulated lipoprotein receptor (LSR) is a cellular receptor for Ib, promoting Ia internalization into a target cell [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clostridium perfringens iota toxin consists of two distinct protein components, one being the cell-binding protein (Ib) and other the enzymatic protein (Ia) [ 1 , 2 , 3 , 4 , 5 , 6 ]. Ia possesses actin-ADP-ribosyltransferase activity, blocking the formation of F-actin in the cytosol and then disrupting the actin cytoskeleton [ 2 , 6 , 7 , 8 ]. It has been reported that lipolysis-stimulated lipoprotein receptor (LSR) is a cellular receptor for Ib, promoting Ia internalization into a target cell [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ia possesses actin-ADP-ribosyltransferase activity, blocking the formation of F-actin in the cytosol and then disrupting the actin cytoskeleton [ 2 , 6 , 7 , 8 ]. It has been reported that lipolysis-stimulated lipoprotein receptor (LSR) is a cellular receptor for Ib, promoting Ia internalization into a target cell [ 6 , 9 ]. Iota toxin is a clostridial binary actin-ADP-ribosylating toxin, which family encompasses Clostridium botulinum C2 toxin (C2I and C2II), Clostridium difficile transferase (CDTa and CDTb), and Clostridium spiroforme toxin (CSTa and CSTb) [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contributions to this Special Issue include several experimental articles, employing sophisticated techniques to gain important insights into the mechanism of cellular entry [1-6]; a thought-provoking perspective comment [7]; and two conceptual reviews, one on apicomplexan pore-forming toxins [8] and one on clostridial binary toxins [9]. What have we learned about the field from this collection?…”
mentioning
confidence: 99%
“…Cellular entry of bacterial toxins utilizes a complex mechanism [8,9] that involves multiple protein partners interacting with each other [3,9] and with a lipid bilayer [1,2,6]. Key players often undergo profound conformational changes, both in aqueous [5] and membranous environments [1,2].…”
mentioning
confidence: 99%
“…Cellular uptake of nanoparticles is a thermodynamic phenomenon that occurs from nanoparticle adsorption on the cell membrane followed by membrane wrapping and invagination in order to minimize the chemical binding energy (114)(115)(116)(117)(118)(119). The distinct organization of MENs around glioblastoma and brain endothelial cells was further verified by fluorescence images of these cells incubated with fluorescein isothiocyanate loaded MENs.…”
Section: Discussionmentioning
confidence: 93%